Peningkatan Aktivitas dan Hasil Belajar Siswa pada Materi Gendang Telinga melalui Pembelajaran Interaktif di Kelas V Sekolah Dasar - Rizki Sahbudin, Susan; Febriyanti, Vina; Fatimah Zahra , Siti; Assidiqi, Asepta; Mufidah Nuha , Ghaida; Gustian Nugraha, Rana (LPPM Universitas PGRI Argopuro Jember, 2026)
ABSTRACT: This study was conducted with the aim of improving student activity and learning outcomes in ear drum material by applying interactive learning in fifth grade elementary school. This study used a classroom action research design with the Kemmis and McTaggart model, which was carried out in two cycles. There were several stages involved, namely planning, implementation of actions, observation, and reflection. The research subjects consisted of eight students. Data were collected through observation, learning outcome tests, and documentation, then analyzed descriptively to compare developments from the pre-cycle to the end of the action. The results of this study successfully showed a significant increase in both aspects measured. The average learning outcome score increased from 37.5 in the pre-cycle to 55 in cycle I and 77.5 in cycle II, with a learning accuracy rate of 87.5% at the end of the action. Student learning activities also improved from an average of 64.58% in cycle I to 85.42% in cycle II, especially in the indicator of concern for ear health, which experienced the most significant increase. These findings successfully demonstrate that interactive media-based learning can generate higher engagement and help students understand the concept of the eardrum more deeply. Thus, interactive learning can be an effective alternative strategy. Keywords: Interactive Learning, Learning Activities, Student Learning Outcomes